Lithium ion battery diaphragm slurry, diaphragm and lithium ion battery
By using furyl hollow polyamide slurry to prepare lithium-ion battery separators, the problems of the separator shrinking at high temperatures and poor wetting on the electrolyte are solved, achieving higher mechanical properties and safety.
Patent Information
- Application Number
- CN202411822260.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
AI Technical Summary
The existing lithium-ion battery separators shrink at high temperatures, affecting battery safety, and have poor wetting properties and poor mechanical properties on the electrolyte.
Using a furyl hollow polyamide slurry, hollow furanyl polyamide nanofibers are prepared by mixing the furyl polyamide solution with ceramic powder, and mixed with a binder and a dispersant to form a slurry with high dispersion and stability and coated on the separator.
It improves the wetting and mechanical properties of the diaphragm to the electrolyte, enhances the heat resistance of the diaphragm and reduces the heat shrinkage rate, and improves the safety and service life of lithium batteries.
Smart Images

Figure CN119708996A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion battery diaphragm slurry, a diaphragm and a lithium ion battery. Background Art
[0002] Since the successful commercialization of lithium cobalt oxide batteries by Sony Corporation of Japan in the 1990s, lithium-ion batteries have continued to develop over the past 30 years and are widely used in new energy vehicles, smart phones, energy storage power stations and other fields, providing many conveniences for people's lives. Lithium-ion batteries are basically composed of positive electrodes, negative electrodes, separators and electrolytes, among which the performance of the separator plays a vital role in the performance of lithium batteries.
[0003] The separator is a thin film sandwiched between the positive and negative electrodes of the battery that acts as an electronic insulator and provides a channel for lithium ion migration. Traditional lithium-ion battery separators are usually polyolefins or coated with a coating layer, but the above separators have a low melting point. When the external temperature is high, the separator will shrink, affecting the safety of the battery.
[0004] In addition, the above-mentioned diaphragms have technical defects such as poor wettability and poor mechanical properties, resulting in poor electrochemical performance of lithium battery diaphragms. In order to improve the performance of the diaphragm, a coating liquid is usually coated on the base film to make a diaphragm. In the existing scheme, the coating liquid can be composed of aramid, polyvinylidene fluoride, ceramics, etc., but aramid has poor solubility in the coating liquid, is difficult to process, and is not easy to degrade.
[0005] Therefore, how to prepare a diaphragm that has high wettability to electrolyte, excellent physical properties, and is environmentally friendly is a technical problem that needs to be solved urgently. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one object of the present invention is to provide a lithium-ion battery diaphragm slurry, a diaphragm and a lithium-ion battery, wherein the diaphragm slurry has stronger dispersibility and stability, and improved moisture permeability, and is applied to the diaphragm to improve the wettability and mechanical properties of the diaphragm to the electrolyte.
[0007] In one aspect of the present invention, the present invention provides a lithium ion battery separator slurry, which is a furan-based hollow polyamide slurry, and the preparation method thereof comprises:
[0008] (1) mixing a furan-based polyamide solution with ceramic powder to obtain a skin solution;
[0009] (2) dissolving octadecane in alcohol to obtain a core layer solution;
[0010] (3) injecting the skin layer solution and the core layer solution into syringes respectively, connecting the outer needle and the inner needle of the coaxial needle respectively, spinning on an electrospinning machine, and then drying, and then removing octadecane to obtain hollow furan-based polyamide nanofibers;
[0011] (4) Mixing the hollow furan-based polyamide nanofibers with a binder and a dispersant to obtain a furan-based hollow polyamide slurry.
[0012] The present invention obtains a cortex solution by mixing a furan-based polyamide solution with ceramic powder. The furan-based polymer has high mechanical properties and can improve the mechanical properties of the diaphragm prepared by subsequent coating. The cortex solution and the core solution are used to prepare hollow furan-based polyamide nanofibers. Ceramic particles are added during the preparation of the hollow fibers. Instead of mixing the prepared hollow fibers with the ceramic particles, the ceramic particles are dispersed on the surface and inside of the hollow fibers to avoid agglomeration of the ceramic particles, improve the dispersion of the furan-based molecular chains, and make the dispersion of the slurry high. At the same time, the generation of hollow fibers can increase the surface area of the slurry in contact with the diaphragm during subsequent coating, thereby effectively improving the wettability of the diaphragm to the electrolyte, and the diaphragm has stronger heat resistance and lower thermal shrinkage.
[0013] In addition, the furan-based hollow polyamide slurry proposed in the present invention may also have the following additional technical features:
[0014] In some embodiments of the present invention, the mass ratio of the furan-based polyamide solution to the ceramic powder is 100:(5-10); the mass ratio of the octadecane to the alcohol is (5-20):100; the mass ratio of the hollow furan-based polyamide nanofibers, the binder and the dispersant is (5-15):(1-4):(2-6).
[0015] In some embodiments of the present invention, in step (1), the method for preparing the furan-based polyamide solution comprises: mixing a dibasic acid containing a furan ring structure, a diamine containing a benzene ring structure and a solvent under an inert atmosphere, and obtaining a furan-based polyamide solution after polymerization.
[0016] In some embodiments of the present invention, the molar ratio of the furan ring-containing dibasic acid to the benzene ring-containing diamine is (1-1.2):1; the mass ratio of the benzene ring-containing diamine to the solvent is 1:(4-10).
[0017] In some embodiments of the present invention, the dibasic acid containing a furan ring structure is one or more of 2,5-furandicarboxylic acid and 3,4-furandicarboxylic acid; the acyl chloride containing a furan ring structure is 2,5-furandicarboxylic acid chloride; and the diamine containing a benzene ring structure is one or more of p-phenylenediamine, m-phenylenediamine, 2,5-diaminobenzenesulfonic acid and 4,4-diaminodiphenyl ether.
[0018] In some embodiments of the present invention, the solvent is one or more of N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, dimethyl phthalate or ethanol; the binder is one or more of polytetrafluoroethylene, polypropylene and carboxymethyl cellulose; the dispersant is one or more of polyvinylpyrrolidone, polymethyl methacrylate, polystyrene, polyvinyl alcohol and polyamide.
[0019] In some embodiments of the present invention, the ceramic powder is one or more of silicon dioxide, aluminum oxide, boehmite, zirconium oxide, magnesium oxide and zinc oxide.
[0020] In some embodiments of the present invention, in step (3), spinning is performed on an electrospinning machine at 15 to 20 kV, and the spinning distance is 12 to 15 cm.
[0021] In some embodiments of the present invention, the feeding rate of the skin solution is 0.4-3 mL / h, and the feeding rate of the core solution is 0.08-0.3 mL / h; the spinning temperature is 30-60°C, the relative humidity is 40-50%, and the spinning time is 4-10 hours.
[0022] In a second aspect of the present invention, a separator is provided, at least one side of which is coated with the lithium-ion battery separator slurry according to any one of claims 1 to 8. The separator has improved wettability to the electrolyte and strong mechanical properties.
[0023] In a third aspect of the present invention, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the above-mentioned separator, thereby improving the safety of the lithium battery.
[0024] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0026] Figure 1 This is a SEM image of the furan-based hollow polyamide fiber prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained commercially.
[0028] Example 1
[0029] 1. Preparation of furan-based polyamide solution: Under a nitrogen atmosphere, 2,5-furandicarboxylic acid chloride and p-phenylenediamine were dissolved in N-methylpyrrolidone at a molar ratio of 1.1:1 and reacted for 4 hours. The mass ratio of p-phenylenediamine to N-methylpyrrolidone was 1:4 to obtain a furan-based polyamide solution.
[0030] 2. Preparation of furan-based hollow polyamide slurry:
[0031] (1) mixing a furan-based polyamide solution and boehmite in a mass ratio of 100:6 to obtain a cortex solution;
[0032] (2) dissolving octadecane in ethanol to obtain a core layer solution with a mass fraction of 5 wt %;
[0033] (3) The skin solution and the core solution were injected into 10 mL syringes respectively, the feeding rate of the skin solution was 0.5 mL / h, and the feeding rate of the core solution was 0.1 mL / h. The outer needle with an inner diameter of 1.01 mm and an outer diameter of 1.49 mm and the inner needle with an inner diameter of 0.41 mm and an outer diameter of 0.72 mm were connected to the coaxial needle respectively, and spinning was performed on an electrospinning machine. The spinning parameters were: the ambient temperature was controlled at 50°C, the relative humidity was 45%, the spinning was performed at 15 kV, the spinning distance was 12 cm, and the spinning time was 4 h; then dried for 24 h to remove the residual solvent, and then the octadecane was removed to obtain hollow furan-based polyamide nanofibers. The SEM image of the obtained hollow fiber is shown in Figure 1 ;
[0034] (4) The hollow furan-based polyamide nanofibers are mixed with polytetrafluoroethylene and polyvinyl pyrrolidone in a mass ratio of 5:2:2 to obtain a furan-based hollow polyamide slurry.
[0035] 3. Preparation of diaphragm: Coat the furan-based hollow polyamide slurry on one side of the PP diaphragm with a coating thickness of 4 μm, and dry to obtain the diaphragm.
[0036] 4. Preparation of lithium batteries: Use the diaphragm to prepare lithium batteries.
[0037] Example 2
[0038] 1. Preparation of furan-based polyamide solution: Under a nitrogen atmosphere, 2,5-furandicarboxylic acid chloride and m-phenylenediamine were dissolved in N-methylpyrrolidone at a molar ratio of 1.2:1 and reacted for 4 hours. The mass ratio of m-phenylenediamine to N-methylpyrrolidone was 1:10 to obtain a furan-based polyamide solution.
[0039] 2. Preparation of furan-based hollow polyamide slurry:
[0040] (1) mixing a furan-based polyamide solution and silicon dioxide in a mass ratio of 100:10 to obtain a cortex solution;
[0041] (2) dissolving octadecane in ethanol to obtain a core layer solution with a mass fraction of 10 wt %;
[0042] (3) The skin solution and the core solution were injected into 10 mL syringes respectively, the feeding rate of the skin solution was 2.5 mL / h, and the feeding rate of the core solution was 0.3 mL / h. The outer needle with an inner diameter of 1.01 mm and an outer diameter of 1.49 mm and the inner needle with an inner diameter of 0.41 mm and an outer diameter of 0.72 mm were connected to the coaxial needle respectively, and spinning was performed on an electrospinning machine. The spinning parameters were as follows: the ambient temperature was controlled at 50°C, the relative humidity was 45%, the spinning was performed at 20 kV, the spinning distance was 15 cm, and the spinning time was 8 h; then dried for 24 h to remove the residual solvent, and then the octadecane was removed to obtain hollow furan-based polyamide nanofibers;
[0043] (4) The hollow furan-based polyamide nanofibers are mixed with polypropylene and polyvinyl alcohol in a mass ratio of 10:3:5 to obtain a furan-based hollow polyamide slurry.
[0044] 3. Preparation of diaphragm: Coat the furan-based hollow polyamide slurry on one side of the PP diaphragm with a coating thickness of 4 μm, and dry to obtain the diaphragm.
[0045] 4. Preparation of lithium batteries: Use the diaphragm to prepare lithium batteries.
[0046] Example 3
[0047] 1. Preparation of furan-based polyamide solution: Under nitrogen atmosphere, 2,5-furandicarboxylic acid chloride and p-phenylenediamine were dissolved in N,N-dimethylformamide at a molar ratio of 1.1:1 and reacted for 6 hours to obtain a furan-based polyamide solution.
[0048] 2. Preparation of furan-based hollow polyamide slurry:
[0049] (1) mixing a furan-based polyamide solution and boehmite in a mass ratio of 100:8 to obtain a cortex solution;
[0050] (2) dissolving octadecane in ethanol to obtain a core layer solution with a mass fraction of 8 wt %;
[0051] (3) The skin solution and the core solution were injected into 10 mL syringes respectively, the feeding rate of the skin solution was 3.5 mL / h, and the feeding rate of the core solution was 0.3 mL / h. The outer needle with an inner diameter of 1.01 mm and an outer diameter of 1.49 mm and the inner needle with an inner diameter of 0.41 mm and an outer diameter of 0.72 mm were connected to the coaxial needle respectively, and spinning was performed on an electrospinning machine. The spinning parameters were: the ambient temperature was controlled at 50°C, the relative humidity was 45%, the spinning was performed at 15 kV, and the spinning distance was 12 cm; then dried for 24 hours to remove the residual solvent, and then the octadecane was removed to obtain hollow furan-based polyamide nanofibers;
[0052] (4) The hollow furan-based polyamide nanofibers are mixed with polytetrafluoroethylene and polyvinyl pyrrolidone in a mass ratio of 5:2:2 to obtain a furan-based hollow polyamide slurry.
[0053] 3. Preparation of diaphragm: Coat the furan-based hollow polyamide slurry on one side of the PP diaphragm with a coating thickness of 4 μm, and dry to obtain the diaphragm.
[0054] 4. Preparation of lithium batteries: Use the diaphragm to prepare lithium batteries.
[0055] Comparative Example 1
[0056] Compared with Example 1, boehmite is added after the hollow furan-based polyamide nanofibers are prepared, that is, in step (4). The specific process is as follows:
[0057] 1. Preparation of furan-based polyamide solution: Under nitrogen atmosphere, 2,5-furandicarboxylic acid and p-phenylenediamine were dissolved in N,N-dimethylformamide at a molar ratio of 1.1:1 and reacted for 6 hours to obtain a furan-based polyamide solution.
[0058] 2. Preparation of furan-based hollow polyamide slurry:
[0059] (1) using the prepared furan-based polyamide solution as a cortex solution;
[0060] (2) dissolving octadecane in ethanol to obtain a core layer solution with a mass fraction of 8 wt %;
[0061] (3) The skin solution and the core solution were injected into 10 mL syringes respectively, the feeding rate of the skin solution was 3.5 mL / h, and the feeding rate of the core solution was 0.3 mL / h. The outer needle with an inner diameter of 1.01 mm and an outer diameter of 1.49 mm and the inner needle with an inner diameter of 0.41 mm and an outer diameter of 0.72 mm were connected to the coaxial needle respectively, and spinning was performed on an electrospinning machine. The spinning parameters were: the ambient temperature was controlled at 50°C, the relative humidity was 45%, the spinning was performed at 15 kV, and the spinning distance was 12 cm; then dried for 24 hours to remove the residual solvent, and then the octadecane was removed to obtain hollow furan-based polyamide nanofibers;
[0062] (4) The hollow furan-based polyamide nanofibers were mixed with polytetrafluoroethylene, polyvinyl pyrrolidone and boehmite in a mass ratio of 5:2:2:0.5 to obtain a furan-based hollow polyamide slurry.
[0063] 3. Preparation of diaphragm: Coat the furan-based hollow polyamide slurry on one side of the PP diaphragm with a coating thickness of 4 μm, and dry to obtain the diaphragm.
[0064] 4. Preparation of lithium batteries: Use the diaphragm to prepare lithium batteries.
[0065] Comparative Example 2
[0066] Compared with Example 1, the prepared furan-based polyamide solution was directly mixed with polytetrafluoroethylene, polyvinyl pyrrolidone and boehmite in a mass ratio of 5:2:2:0.5 to obtain a slurry, which was then coated on one side of the PP separator. The specific process was as follows:
[0067] 1. Preparation of furan-based polyamide solution: Under nitrogen atmosphere, 2,5-furandicarboxylic acid and p-phenylenediamine were dissolved in N,N-dimethylformamide at a molar ratio of 1.1:1 and reacted for 6 hours to obtain a furan-based polyamide solution.
[0068] 2. Prepare slurry: mix the furan-based polyamide solution with polytetrafluoroethylene, polyvinyl pyrrolidone and boehmite in a mass ratio of 5:2:2:0.5 to obtain slurry.
[0069] 3. Preparation of diaphragm: Coat the above on one side of PP diaphragm with a coating thickness of 4 μm, and dry to obtain diaphragm.
[0070] 4. Preparation of lithium batteries: Use the diaphragm to prepare lithium batteries.
[0071] The membranes prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to wettability tests, puncture strength tests, and air permeability tests, and their thermal shrinkage rates were measured at 120° C. The test data results are shown in Table 1.
[0072] Table 1
[0073]
[0074] From the wettability data, the wettability of the diaphragms prepared in Examples 1-3 is significantly better than that of the diaphragms prepared in Comparative Examples 1 and 2. In Comparative Example 1, the ceramic particles were added after the hollow fibers were prepared, resulting in a significant increase in its air permeability and thermal shrinkage. The contact angle of the diaphragm prepared in Comparative Example 2 to the electrolyte was significantly larger. It is speculated that the reason is that the hollow fibers were not prepared in Comparative Example 2, resulting in a decrease in its surface area and a significant decrease in wettability to the diaphragm.
[0075] In summary, in the process of preparing hollow fibers, ceramic particles are added to obtain a slurry, which is then coated on a base membrane to obtain a diaphragm. The diaphragm has significantly improved wettability to the electrolyte, high mechanical strength, and significantly enhanced air permeability. Applying it to batteries will improve the safety and service life of the batteries, and will be beneficial to the further development of the battery industry.
[0076] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0077] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A lithium ion battery separator slurry, characterized in that: The slurry is a furan-based hollow polyamide slurry, and the preparation method thereof comprises: (1) mixing a furan-based polyamide solution with ceramic powder to obtain a skin solution; (2) dissolving octadecane in alcohol to obtain a core layer solution; (3) injecting the skin layer solution and the core layer solution into syringes respectively, connecting the outer needle and the inner needle of the coaxial needle respectively, spinning on an electrospinning machine, and then drying, and then removing octadecane to obtain hollow furan-based polyamide nanofibers; (4) Mixing the hollow furan-based polyamide nanofibers with a binder and a dispersant to obtain a furan-based hollow polyamide slurry.
2. The lithium-ion battery separator slurry according to claim 1, characterized in that: In step (1), the mass ratio of the furan-based polyamide solution to the ceramic powder is 100:(5-10); In step (2), the mass ratio of the octadecane to the alcohol is (5-20):100; In step (4), the mass ratio of the hollow furan-based polyamide nanofibers, the binder and the dispersant is (5-15):(1-4):(2-6).
3. The lithium-ion battery separator slurry according to claim 1, characterized in that: In step (1), the method for preparing the furan-based polyamide solution comprises: mixing a dibasic acid containing a furan ring structure, a diamine containing a benzene ring structure and a solvent under an inert atmosphere, and obtaining a furan-based polyamide solution after polymerization.
4. The lithium-ion battery separator slurry according to claim 3, characterized in that: The molar ratio of the furan ring-containing dibasic acid or the furan ring-containing acyl chloride to the benzene ring-containing diamine is (1-1.2):1; The mass ratio of the diamine containing a benzene ring structure to the solvent is 1:(4-10).
5. The lithium-ion battery separator slurry according to claim 3, characterized in that: The dibasic acid containing a furan ring structure is one or more of 2,5-furandicarboxylic acid and 3,4-furandicarboxylic acid, and the acyl chloride containing a furan ring structure is 2,5-furandicarboxylic acid chloride; The diamine containing a benzene ring structure is one or more of p-phenylenediamine, m-phenylenediamine, 2,5-diaminobenzenesulfonic acid and 4,4-diaminodiphenyl ether.
6. The lithium-ion battery separator slurry according to claim 3, characterized in that: The solvent is one or more of N-methylpyrrolidone, dimethylacetamide, N,N-dimethylformamide, dimethyl phthalate or ethanol; The binder is one or more of polytetrafluoroethylene, polypropylene and carboxymethyl cellulose; The dispersant is one or more of polyvinyl pyrrolidone, polymethyl methacrylate, polystyrene, polyvinyl alcohol and polyamide.
7. The lithium-ion battery separator slurry according to claim 1, characterized in that: In step (3), spinning is performed on an electrospinning machine at 15 to 20 kV, a spinning distance of 12 to 15 cm, a spinning temperature of 30 to 60° C., a relative humidity of 40 to 50%, and a spinning time of 4 to 10 hours.
8. The lithium-ion battery separator slurry according to claim 1, characterized in that: In step (3), the feeding rate of the skin layer solution is 0.4-3 mL / h, and the feeding rate of the core layer solution is 0.08-0.3 mL / h.
9. A diaphragm, characterized in that: At least one side of the separator is coated with the lithium-ion battery separator slurry according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The diaphragm according to claim 9 is included.
Citation Information
Cited By
Lithium battery diaphragm coating based on nano material and application thereof
CN120484583A
A lithium battery diaphragm coating based on nanomaterials and its application
CN120484583B